Impact of pubic access to computers and Internet on the connectedness of rural Malaysians - Alias, Nor Aziah; Mohd Noor, Marhaini; Proenza, Francisco J.; Jamaludin, Haziah; Ismail, Izaham Shah; Hashim, Sulaiman (MIT Press, 2015)
This chapter reports the findings of research conducted in 2010 on the connectedness of rural Malaysians who accessed computers and the Internet through the rural Internet centers (RICs) established by the Malaysian government in 2000 and 2003. We examine the impact of the RICs on users’ sense of social connectedness, defined as the feeling of belongingness and being linked and related to a network, community, or group that one trusts and interacts with. Our study’s findings give credence to the RIC initiative. Users use RIC facilities and services to connect with family, friends, and acquaintances, with new people external to their social circle, and (albeit to a much lesser degree) with government. Users perceive a heightened sense of connectedness and feel that this connectedness has had a positive impact in their lives. There appears to be room to expand the impact of RIC telecenters so that they foster greater collaboration and help nurture the development of positive social capital. Some of the possibilities for expanding impact are identified.